Dampak Struktur Modal dan Profitabilitas Terhadap Nilai Perusahaan Sektor Properti, Real Estate dan Konstruksi Bangunan - Imam Buchari (Business Management Journal, 2021)
This study aims to determine whether the capital structure (DER) and profitability (ROE) have an impact on the Company Value (PBV) of the property, real estate and building construction sectors listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 period. The research method used is Time Series from 2012-2018 and the number of Cross Sections as many as 10 companies, with the ex post facto method. The data presented annually are obtained from annual reports and financial reports of 10 property, real estate and building construction companies listed on the Indonesia Stock Exchange. This study uses a panel effects data regression model with a fixed effect model as a result of selecting the best regression model. Based on the results of the analysis, it can be concluded that DER partially has a positive and significant influence on firm value (PBV). To increase firm value, all companies in this sector are advised to strengthen their capital structure by increasing DER. Although most of these companies have DER> 1x, the results of the research show the positive influence shown by DER on PBVR, this means that the use of corporate debt to increase company equity is still quite controlled, so that the financial leverage of companies in this sector is still quite safe in using debt. company to increase company value. The company still has the potential to increase firm value by increasing the company's DER as long as the total debt does not exceed the company's total equity. then ROE partially has a positive and significant effect on Firm Value (PBV). So that to increase profitability is done by increasing the ROE indicator so that the Firm Value (PBV) can increase. Increase ROE in various ways, such as increasing company efficiency, reducing non-essential costs, maximizing the company's equity capacity and developing strategies to increase the company's net income so that it can increase the Company's ROE. DER and ROE simultaneously have a significant effect on Firm Value (PBV).Keywords:  Capital Structure, Firm Value, Debt to Equity ratio, Price to Book Value, Profitability, Return on Equity